1989
DOI: 10.1002/chin.198937031
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: A Comparative Study of the Oxidation Resistance of Zirconium Carbide and Zirconium Oxide Carbide.

Abstract: A comparative investigation of the oxidation kinetics of ZrC0.963 and powders of the compositions ZrC0.79O0.10 and ZrC0.67O0.22 in the temp. range 400‐1000 °C under 100 torr O2 pressure shows that the oxidation becomes important above 400‐500 °C and that the oxidation resistance slightly decreases in the order ZrC0.963 > ZrC0.79O0.10 > ZrC0.67O0.22.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The oxidation of ZrC has been studied under several experimental conditions of temperature and pressure but a clear understanding has not yet been achieved due to the large numbers of variables that affect it, such as chemical composition of the initial material (C/Zr stoichiometry), porosity, or grain size …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The oxidation of ZrC has been studied under several experimental conditions of temperature and pressure but a clear understanding has not yet been achieved due to the large numbers of variables that affect it, such as chemical composition of the initial material (C/Zr stoichiometry), porosity, or grain size …”
Section: Introductionmentioning
confidence: 99%
“…3,4 ZrC has better properties than other carbides such as a higher thermal conductivity and higher melting point, [5][6][7][8] however, a comprehensive database on its properties is not available and therefore its use is rarely considered. 9 The oxidation of ZrC has been studied [10][11][12][13][14][15][16][17][18][19] under several experimental conditions of temperature and pressure [10][11][12][13][14] but a clear understanding has not yet been achieved due to the large numbers of variables that affect it, such as chemical composition of the initial material (C/Zr stoichiometry), porosity, or grain size. 9,20 A mechanistic model recently proposed by Katoh et al 9 building on the model previously proposed by Shimada 21 showed as an initial stage the formation of an oxycarbide ZrO x C (1Àx) layer 9,10,22 prior to the formation of an oxide layer.…”
mentioning
confidence: 99%
“…in controlling phase contamination due to the solubility of oxygen and nitrogen in the ZrC x lattice. Additionally, the presence of oxygen in ZrC x lattice gives birth to the oxycarbide class of compounds where there is a direct substitution of carbon (or a carbon vacancy) by oxygen [17][18][19] . It is also possible for carbon or oxygen to occupy the octahedral interstitial vacancies of the Zr lattice 20,21 .…”
mentioning
confidence: 99%
“…The wetting angle for Co and Ni is higher for ZrC x O y than for ZrC, which make zirconium oxycarbides more stable in liquid transition metals, Figure 23. Coefficient of thermal expansion (10 −6 K −1 ) 10 6.8 7.1-8.6 42 Thermal conductivity (W m −1 K −1 ) 2 2 1 3 -5 58 Electrical resistivity (Ω cm) However, it was reported that the oxidation of zirconium oxycarbides starts below 500 • C. 107,108 Zirconium oxycarbide already forms at 400-480 • C within 5-10 min as an intermediate product of the oxidation of ZrC forming ZrC 1−y O y . [109][110][111] Besides the diffusion process of oxygen in zirconium carbide, 23 generally, it is accepted that ZrC is completely oxidized upon reaching 1000 • C. 112 ZrC 0.625 O 0.500 and ZrC 0.571 O 0.143 phases formed at 1127 • C under pressure of oxygen P O2 = 10 −3 -10 −7 Pa. 22 Processes connected with the grain boundary diffusion of oxygen could play a role in the formation of zirconium oxycarbides.…”
Section: Properties Of Sintered Materialsmentioning
confidence: 99%
“…The wetting angle for Co and Ni is higher for ZrC x O y than for ZrC, which make zirconium oxycarbides more stable in liquid transition metals, Figure 23 98 . However, it was reported that the oxidation of zirconium oxycarbides starts below 500°C 107,108 . Zirconium oxycarbide already forms at 400–480°C within 5–10 min as an intermediate product of the oxidation of ZrC forming ZrC 1− y O y 109–111 .…”
Section: Ternary Compoundsmentioning
confidence: 99%